2017
DOI: 10.1186/s12859-016-1449-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative visualization of protein secondary structures

Abstract: BackgroundProtein function is determined by many factors, namely by its constitution, spatial arrangement, and dynamic behavior. Studying these factors helps the biochemists and biologists to better understand the protein behavior and to design proteins with modified properties. One of the most common approaches to these studies is to compare the protein structure with other molecules and to reveal similarities and differences in their polypeptide chains.ResultsWe support the comparison process by proposing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…It is worth noting that the secondary structure of the keratin changes significantly after 60 ns. It has been reported that the components ratio of the secondary structure is bound to influence the volume, shape, and biological functions of proteins [58], which are needed for the maintenance of the keratin structure integrity, and hinting that their variations are a critical parameter to evaluate the nanotoxicity of PG and GO materials on proteins. Our results, GO is more biocompatible than PG, are consistent with prior research [12,55,59,60].…”
Section: Secondary Structure Changes Of the Keratinmentioning
confidence: 99%
“…It is worth noting that the secondary structure of the keratin changes significantly after 60 ns. It has been reported that the components ratio of the secondary structure is bound to influence the volume, shape, and biological functions of proteins [58], which are needed for the maintenance of the keratin structure integrity, and hinting that their variations are a critical parameter to evaluate the nanotoxicity of PG and GO materials on proteins. Our results, GO is more biocompatible than PG, are consistent with prior research [12,55,59,60].…”
Section: Secondary Structure Changes Of the Keratinmentioning
confidence: 99%
“…Users can generate realistic millisecond-scale representations of conformational changes in proteins. Kocincová et al, 2017 introduce a visualization approach that addresses the divide between commonly used 1D and 3D representations. By incorporating details about the mutual positions of protein chains into the 1D sequential representation, users can observe spatial differences between proteins without the typical occlusion found in a 3D view.…”
Section: Scaling Up To Simulation Ensembles and Data Sharingmentioning
confidence: 99%
“…Comparing complex 3D structures is a difficult task and may be solved by switching to a more simple representation. Recent work by Kocincová et al [KJB*17], for instance, tackles this task by bridging between 1D amino acid sequences and their 3D‐representations. This is useful to compare time‐steps of a MD simulation of the same sequence, but fails to capture global correlations between the changes of individual elements of the sequence.…”
Section: Related Workmentioning
confidence: 99%